The effects of stance width during barbell hip thrust on power and velocity output among adolescent Silat athletes - Muhammad Zulqarnain Mohd Nasir; Ali Md Nadzalan; Abdul Muiz Nor Azmi; Mohd Aizzat Adnan (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim. In the physically demanding combat sport of Silat, strength and power dominate. Consequently, applying various stance widths during barbell hip thrusts may tailor athletes' lower-body exercises to individual needs. This has the potential to optimize performance. The aim of this study is to investigate the impact on performance of power, speed, and stance width among Silat combat athletes.